How to thrive in unstable environments: Gene expression profile of a riparian earthworm under abiotic stress - Sosa, Irene de; Verdes, Aída; Tilikj, Natasha; Marchán, Daniel F.; Planelló, Rosario; Herrero, Oscar; Almodóvar Pérez, Ana María; Díaz Cosín, Darío J.; Novo Rodríguez, Marta (Science of The Total Environment, 2022)
Nowadays, extreme weather events caused by climate change are becoming more frequent. This leads to the occurrence of extreme habitats to which species must adapt. This challenge becomes crucial for species living in unstable environments, such as the riparian earthworm Eiseniella tetraedra. Its cosmopolitan distribution exposes it to various environmental changes, such as freezing in subarctic regions or droughts in Mediterranean areas. Transcriptional changes under cold and desiccation conditions could therefore shed light on the adaptive mechanisms of this species. An experiment was performed for each condition. In the cold experiment, the temperature was lowered to −14 °C ± 2 °C (compared to 8 °C for control samples), and in the desiccation treatment, humidity was lowered from 60% to 15%. Comparisons of gene expression levels between earthworms under freezing conditions and control earthworms revealed a total of 84 differentially expressed genes and comparisons between the desiccation experiment and the control yielded 163 differentially expressed genes. However, no common responses were found between the two treatments. The results suggest that E. tetraedra can acclimate to low temperatures due to the upregulation of genes involved in glucose accumulation. However, downregulation of the respiratory chain suggests that this earthworm does not tolerate freezing conditions. Under desiccation conditions, genes involved in cell protection from apoptosis and DNA repair were upregulated. In contrast, lipid metabolism was downregulated, presumably to conserve resources by reducing the rate at which they are consumed.